2015
DOI: 10.1128/jvi.01630-15
|View full text |Cite
|
Sign up to set email alerts
|

Replication and Transmission of the Novel Bovine Influenza D Virus in a Guinea Pig Model

Abstract: Influenza D virus (FLUDV) is a novel influenza virus that infects cattle and swine. The goal of this study was to investigate the replication and transmission of bovine FLUDV in guinea pigs. Following direct intranasal inoculation of animals, the virus was detected in nasal washes of infected animals during the first 7 days postinfection. High viral titers were obtained from nasal turbinates and lung tissues of directly inoculated animals. Further, bovine FLUDV was able to transmit from the infected guinea pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
73
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 28 publications
(60 reference statements)
5
73
0
5
Order By: Relevance
“…The age of cattle used in the experiments could account for such a discrepancy, and it is also notable that our calves were naturally born and given thawed colostrum at birth. On the other hand, our data are similar to swine and ferret IDV experimental infection models but unlike an IDV guinea pig model in which the highest viral titer was found in lung tissue despite intranasal inoculation (11). Structural modeling suggested that, similar to ICV, IDV binds to 9-O-acetyl sialic acid (1).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The age of cattle used in the experiments could account for such a discrepancy, and it is also notable that our calves were naturally born and given thawed colostrum at birth. On the other hand, our data are similar to swine and ferret IDV experimental infection models but unlike an IDV guinea pig model in which the highest viral titer was found in lung tissue despite intranasal inoculation (11). Structural modeling suggested that, similar to ICV, IDV binds to 9-O-acetyl sialic acid (1).…”
Section: Discussionsupporting
confidence: 66%
“…IDV was detected in nasal turbinate, trachea, bronchus, and right medial lung lobe tissues collected at 4 dpi, and IHC confirmed the presence of IDV antigen in all the tissues except RMD. In other animal models, IDV was shown to replicate within the nasal turbinate; could be detected in nasal washes from infected swine, ferret, and guinea pig; and could also be transmitted through direct contact among members of the same species (1,11). We were able to detect IDV in the right medial lung lobe at 4 dpi via both quantitative RT-PCR and TCID 50 , but no antigen was seen via IHC and there was no evidence of pulmonary pathology, again suggestive of an upper respiratory tract infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(24) zakazili donosowo świnki morskie IDV. W tej samej klatce umieścili zwierzęta kontrolne, celem oceny możliwości zakażenia drogą kontaktu bezpośredniego.…”
unclassified